Mandela and excellent African leadership: Theory and lessons for practice from an appreciative thematic analysis. Issue 2 (2nd July 2016) - Chasi, Colin; Levy, Neil
ABSTRACT: Nelson Mandela is highly regarded as an example of excellent leadership. Yet little has been done in communication studies to describe his leadership communication. Significantly, little has been done to locate and to theorise about his leadership style in relation to the African moral philosophy of ubuntu . the article presents an appreciative thematic analysis of how Mandela's leadership communication practices were eulogised in tributes written in his memory in selected South African newspapers. An innovative method of appreciative thematic enquiry is used to arrive at three key themes of praise for the leadership of Mandela. Lessons for leadership are drawn out and highlighted.